Does the Adoption of International Standards Affect Audit Quality? - Devianti Yunita Harahap, Cahya Irawady, Djoemarma Bede, (Opción, 2019)
This study employs a descriptive method by using the survey research approach and uses the regression analysis to investigate the empirical data. Independent variable of this research is the implementation of auditing standards that emphasized on ISAs, while the dependent variable is audit quality based on quality indicators around balanced scorecard with four categories: inputs, process, outcomes, and context. The result showed that the implementation of auditing standards based on ISAs has a significant influence on audit quality. Also, the audit firm’s audit quality is already well, but the ISAs provide the legal force to reduce standards violation.